Teaching militant humility against the aggressions of a neoliberal world. Issue 5 (3rd September 2022) - Säfström, Carl Anders
ABSTRACT: This article develops a militant teaching humility regarding the foundational aggression and violence of a neoliberal worldview within late capitalism. Mainly the article shows how such aggressions and violence take shape as schooling the self-interested consumer within a school market. This article also shows how such self-interest understands education in terms of individualism, comparison, and competition, ultimately leading to the destruction of the social fabric of the common good of democracies. The teaching strategy identified highlights the humility and discipline needed to transform the aggression and violence of late capitalism into a non-violent but consistent strategy for democratization. The strategy developed in the article takes inspiration from Judith Butler, Jacques Rancière and Thich Nhat Hanh, and exemplifies what democratization in education implies today. This article concludes with teaching understood as an ethical and political concern in being for the other, in being interested in the freedom of the other.